Autistic women's experience of intimate relationships: the impact of an adult diagnosis. Issue 1 (28th February 2019) - Kock, Elizabeth; Strydom, Andre; O'Brady, Deirdre; Tantam, Digby
Abstract : Purpose: The purpose of this paper is to explore the experience of intimate relationships of women who have been diagnosed with Autism in adulthood. Design/methodology/approach: Semi-structured interviews were used to interview eight participants. The data were transcribed and analysed using the interpretative phenomenological analysis method. Findings: Four overall themes were identified. These included "Response to the diagnosis and receiving more information about Autism", "Factors influencing dating behaviour", "Sex and sexual experiences" and "Experience of intimate relationships as a person with Autism". Research limitations/implications: The results of this study have implications for both research and clinical practice as it highlights the areas in which women newly diagnosed with autism spectrum disorder (ASD) could benefit from support. Practical implications: The study hopes to add to the limited existing research on adult women with ASD. Originality/value: To date no similar research has investigated the same phenomenon through a similar method.